Menangani cabaran umat Islam era moden (addressing challenges of Muslims in modern era) - Nor, M.R.M. (Dept. of Islamic History and Civilization, Academy of Islamic Studies, University of Malaya, Kuala Lumpur, 2011)
In modern era, Muslims are faced with various challenges which need to be addressed. This is in order to resolve the issues related to them properly instead of becoming cancerous bodies in the public life. This paper seeks to explain some of the challenges Muslims encounter in Southeast Asia, especially in Malaysia. This paper discusses some those challenges and proposes some solutions accordingly.